Rasch Analysis On Investment Decision Anomalies in Indonesian Islamic capital market - Dr. Darmawan Darmawan, SPd.,MAB (Universitas Pendidikan Indonesia, 2022)
Purpose – This Research aims to understand what behavioural anomalies are in making investment decisions in the Indonesian Islamic capital market and what factors are behavioural anomalies in making investment decisions in the Indonesian Islamic capital market.Methodology - This Research uses a quantitative approach by applying Rasch analysis to measure five types of investment behaviour anomalies. Data was collected using a questionnaire. Findings - The endowment and its items are considered the primary considerations for investors. On the other hand, Anchoring and Adjustment of all the items are not considered the primary consideration. Meanwhile, Conservatism, Optimism and Hindsight spread to both categories of items. The difference in responses by gender was found that only on the item, Feeling greater comfort and optimism with their employer's stock, felt that investing there was less risky than investing elsewhere. Meanwhile, the difference in responses based on age was found that the age of thirties most often gave a different response from other respondents, especially in the indications of Endowment and Hindsight. In comparison, the difference in responses at the age of forties occurred in the items indicating optimism. Financial service providers are advised to offer the most suitable financial products based on gender differences. The most important thing is that in their thirties, an age group that tends to maintain their investment for a longer time and that investment decisions and risks in share ownership where they work are responded differently by gender. Novelty – This research is the first to use the Rasch model in an effort to understand the anomaly of investor behavior in Indonesia. Research Limitation - The anomaly tested does not cover all investor behavior anomalies based on Pompian's behavioral theory. However, only the most representative behavioral anomaly is selected.Research Implication - The results of this study are especially important for companies in the Islamic capital market in Indonesia to be able to attract potential investors and retain existing investors.